DOCOMOMO. Modern architecture and heritage - María Teresa Palomares Figueres (Loggia, Arquitectura & Restauración, 2018)
The international organisation DoCoMoMo, founded in 1988 in Holland by the architects Hubert-Jan Henket and Wessel de Jonge, is renowned worldwide for its guardianship of modern architectural heritage. This article summarises the history of this organization and its links with UNESCO for adding works of the Modern Movement to the World Heritage List where, recently, the work of Le Corbusier has been incorporated. Special attention has been paid to protecting small-scale modern heritage, the contributions of national committees in the corresponding registers being of great importance to this task. Among those committees, the Iberian DoCoMoMo is worthy of mention for having documented more than 1,200 works in the different Registers of Modern Architecture from 1925 to 1965.